2017
DOI: 10.1126/science.aan6516
|View full text |Cite
|
Sign up to set email alerts
|

The condensin complex is a mechanochemical motor that translocates along DNA

Abstract: Condensin plays crucial roles in chromosome organization and compaction, but the mechanistic basis for its functions remains obscure. We used single-molecule imaging to demonstrate that Saccharomyces cerevisiae condensin is a molecular motor capable of adenosine triphosphate hydrolysis–dependent translocation along double-stranded DNA. Condensin’s translocation activity is rapid and highly processive, with individual complexes traveling an average distance of ≥10 kilobases at a velocity of ~60 base pairs per s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

11
230
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 291 publications
(241 citation statements)
references
References 44 publications
11
230
0
Order By: Relevance
“…Even without any cooperative interaction between SMCs, “loop-extrusion” dynamics could drive condensin accumulation at the bases of chromatin loop domains while compacting chromosomes (Alipour and Marko, 2012, Goloborodko et al, 2016b, Goloborodko et al, 2016a). Single-molecule experiments have indeed observed DNA translocation (Terakawa et al, 2017) and loop-extrusion (Ganji et al, 2018) dynamics for yeast condensin, supporting this model. A possible molecular mechanism underlying loop extrusion by condensin which is consistent with the observations of (Ganji et al, 2018) has been presented in (Lawrimore et al, 2017).…”
Section: Discussionmentioning
confidence: 58%
“…Even without any cooperative interaction between SMCs, “loop-extrusion” dynamics could drive condensin accumulation at the bases of chromatin loop domains while compacting chromosomes (Alipour and Marko, 2012, Goloborodko et al, 2016b, Goloborodko et al, 2016a). Single-molecule experiments have indeed observed DNA translocation (Terakawa et al, 2017) and loop-extrusion (Ganji et al, 2018) dynamics for yeast condensin, supporting this model. A possible molecular mechanism underlying loop extrusion by condensin which is consistent with the observations of (Ganji et al, 2018) has been presented in (Lawrimore et al, 2017).…”
Section: Discussionmentioning
confidence: 58%
“…Indeed, it has been shown that condensin from Saccharomyces cerevisiae is a molecular motor capable of ATP hydrolysis-dependent translocation along double-stranded DNA in vitro , using DNA curtains at a velocity of ∼60 base pairs per second (60). An argument against this model is the relative low ATPase activity of Smc (3) compared to other nucleic acid motor proteins.…”
Section: Discussionmentioning
confidence: 99%
“…Purified budding yeast condensin promotes the formation and enlargement of DNA loops in an ATP-dependent manner [81]. In a different experimental setting, condensin has also been shown to translocate along DNA unidirectionally, which requires its intact ATPase [82]. These studies have suggested that condensin functions as an active machine to mediate DNA loop extrusion.…”
Section: Intrachromosomal Interactions: Another Open Questionmentioning
confidence: 99%
“…However, in contrast to budding yeast condensin, ATP-dependent, unidirectional translocations have not been seen for both the fission yeast and human cohesins [19,20,50]. It should also be noted that the purified budding yeast condensin can tether two intermolecular DNA strands [82]. Thus, cohesin and condensin might be equipped with activities for both stochastic interactions and loop extrusions.…”
Section: Intrachromosomal Interactions: Another Open Questionmentioning
confidence: 99%